Formulation and Evaluation of Atenolol Floating Tablets Using Different Polymers: Guargum, Sodium Alginate, Hpmc100cps and Carbopol940 - Eswer, Goyal (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT: The objective of the present study was to prepare Floating tablets of Atenolol with best polymer. These were developed to prolong the gastric residence time and increase the drug bioavailability .The Tablets were prepared by direct compression technique, using polymers such as Guar gum, Sodium alginate, HPMC-100CPS, Carbopol940, and other standard excipients. Tablets were evaluated for a physical characteristic was evaluated. Hardness, floating capacity, thickness, weight variation and dissolution. Among four polymers studied, Sodium alginate had shown more drug release. Among eight formulations, one (F6) was found to be best of all the trials showing that the drug release matches the brand product.